2012
DOI: 10.1177/000313481207800439
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Assessment of the Inferior Vena Cava: Useful Tool for the Evaluation of Fluid Status in Critically Ill Patients

Abstract: Inferior vena cava (IVC) diameter change on limited transthoracic echocardiogram (LTTE) can provide a useful guide of fluid status evaluation in critically ill patients. Institutional review board approval was obtained. Prospective evaluation of hemodynamic status was performed in hypotensive patients via LTTE. Images were obtained using an ultrasound machine without M-mode capability. Qualitative assessment of the IVC was obtained via subxyphoid window. FLAT IVC was defined as diameter less than 2 cm and FAT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(42 citation statements)
references
References 24 publications
2
36
1
3
Order By: Relevance
“…For this reason, the collapsibility index (reflecting the degree of vessel collapse during intrathoracic pressure changes of the respiratory cycle) is a useful measure for estimating cardiac preload. A collapsibility index of greater than 50% in nonpregnant patients along with a decreased IVC diameter of less than 2.1 cm suggests hypovolemia 7 . In our study, the collapsibility index ranged from 14% to 18% and did not change significantly with volume infusion, suggesting that central venous pressure was maintained across the spectrum of volume changes we evaluated.…”
Section: Discussionmentioning
confidence: 43%
“…For this reason, the collapsibility index (reflecting the degree of vessel collapse during intrathoracic pressure changes of the respiratory cycle) is a useful measure for estimating cardiac preload. A collapsibility index of greater than 50% in nonpregnant patients along with a decreased IVC diameter of less than 2.1 cm suggests hypovolemia 7 . In our study, the collapsibility index ranged from 14% to 18% and did not change significantly with volume infusion, suggesting that central venous pressure was maintained across the spectrum of volume changes we evaluated.…”
Section: Discussionmentioning
confidence: 43%
“…Ähnliche Ergebnisse werden von Chen et al und Modi dargestellt, die eine signifikante Korrelation von Index IVC/ Ao zum Grad des Wasserverlustes bei Säuglingen aufzeigen konnten [23,24]. Ebenso wird für Erwachsene das genannte sonografische Verfahren durch eine größere Anzahl von Arbeitsgruppen als relevante Methode zu Beurteilung der Volumensituation beschrieben [9,16,25,26,27]. Keine der zitierten Arbeiten bezieht jedoch Neugeborene in die Untersuchungen ein.…”
Section: Diskussionunclassified
“…4,8,9,10 The qualitative assessment of DCIIVC has also been carried out in a prospective study and demonstrated that DCIIVC offers a rapid, non-invasive way to evaluate VS in critically ill patients. 11 Despite its accuracy and usefulness, DCIIVC is not widely used as a clinical indicator for FR.…”
Section: Discussionmentioning
confidence: 99%